GOOD CORPORATE GOVERNANCE DAN PRAKTEK PENGHINDARAN PAJAK (TAX AVOIDANCE) - Wirmie Eka Putra (Jurnal Manajemen Terapan dan Keuangan, 2021)
This study aims to determine the effect of corporate governance variables consisting of managerial ownership, institutional ownership, and the proportion of independent board of commissioners and audit committee and audit quality on tax avoidance (Empirical Study of Banking Companies listed on the IDX 2015-2019). The population of this research is banking companies listed on the IDX in 2015-2019. The sampling technique used purposive sampling. Forty companies met the criteria as samples and took five years of research, so the research data was 40 x 5, which amounted to 200. The software used for data processing was SPSS version 22. The results of this study are that the corporate governance variable, which consists of institutional ownership, the audit committee, and audit quality affects tax avoidance. Meanwhile, managerial ownership and the proportion of independent commissioners do not affect tax avoidance.